Demographic and neuropsychological profile of HIV-positive children referred for an assessment at a local clinic over a 5-year period - Mokoena, Limpho (Department of Psychology, 2025)
Individuals in low- and middle-income countries (LMICs) are disproportionately affected by the human immunodeficiency virus (HIV) relative to high-income countries (HICs). Children are particularly vulnerable given the impact of HIV on brain development. Neuropsychology is still in its infancy in South Africa and there are limited services dedicated to addressing neuropsychological difficulties, including the assessment of children living with HIV. At the pediatric neuropsychology clinic (PNC) at the Red Cross War Memorial Children's Hospital (RXH) in Cape Town, South Africa, free services related to neuropsychological assessments are available to those referred by health professionals, an offering that is rare in South Africa. Considering the impact of HIV on the brain, the PNC offers services and resources to support the study of the effect of HIV (and other pathologies that result in neuropsychological impairments) on the developing brain and its influence on children more broadly in the South African context. Given how limited such services of this nature are in this context and the related opportunity for research and knowledge based on such services, I aimed to the describe the demographic, medical, developmental, and neuropsychological profiles of children referred to RXH PNC over a 5-year period (with an in depth focus on those who are HIV-positive). I investigated a series of neuropsychological reports from the PNC, retrospectively from the year 2012 to 2016, using qualitative and quantitative methods. I report on all the children referred to the clinic within this period (N= 158) and then specifically report in depth on the proportion of children who were HIV-positive (n= 73, 45%) and describe their demographic profiles. I then compared the neuropsychological outcomes of the HIV-Positive Subsample to a separate demographically matched typically developing Control Group (n=41) recruited from local communities. Overall, there were no significant differences in the demographic profile between the HIV- Positive Subsample and the Control Group. However, in the neuropsychological profile there were significant differences found between these two groups in all of the neuropsychological domains except visual memory. The evidence from this study supported the association between cognitive deficits found in children with HIV often discussed in literature. Given the dearth of specialist neuropsychological assessment facilities that are accessible to the public, this highlights the importance of clinics such as the PNC. More specifically the PNC is at the forefront of providing pediatric neuropsychology services in South Africa. The benefits of the PNC include a hub for data of cognitive fall out seen at the clinic which can inform research and other collaborative projects with clinicians and universities. Further, having detailed neuropsychological and demographic profiles/data of children living with HIV can inform intervention-based studies. Intervention-based studies can include a practical component in assisting HIV-positive children attaining a better quality of life considering their neuropsychological difficulties.